ANALYSIS OF FIXED CARBON AND VOLATILE MATTER BRIQUETTES OF PINE SAWDUST AND COCONUT SHELL WASTE - Dewi, Rany Puspita; Sumardi, Sumardi; Isnanto, Rizal (Jurnal Rekayasa Mesin, 2023)
Briquetting technology became one appropriate method that can be used to convert biomass waste into a renewable energy source. Sources of biomass raw materials that have promising potential are pine sawdust and coconut shell waste. Sawdust has potential for about 0.78 million m3/year and coconut shell waste around 360 thousand tons/year. The research aim was to analyse the effect of the carbonization temperature to volatile matter and fixed carbon of briquette. The research was done by variating carbonization temperature at 400 oC, 500 oC, and 600 oC. The result showed that at carbonization temperature of 400 oC, the volatile matter and fixed carbon was 42.28% and 55.74%. The volatile matter and fixed carbon are 43.19% and 54.96%, found at carbonization temperature 500 oC. The highest fixed carbon 55.98% and the lowest volatile matter 42.19% was found from carbonization temperature at 600 oC. The carbonization temperature in briquetting process affects the volatile matter and fixed carbon of briquette.